2012
DOI: 10.1037/a0024922
|View full text |Cite
|
Sign up to set email alerts
|

Illusory contour figures are perceived as occluding contours by 4-month-old infants.

Abstract: Although 4-month-olds perceive continuity of an object's trajectory through occlusion, little is known about the information specifying an occluding surface at this age. We investigated this in 3 experiments involving 84 participants. Testing the claim that 5-month-olds are unable to perceive the Kanizsa figure as an occluding surface (Csibra, 2001), we demonstrated that 4-month-olds perceived trajectory continuity behind this figure providing its horizontal extent was small. We demonstrated that the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 33 publications
1
24
1
Order By: Relevance
“…However, this profile for the later development of global perceptual abilities is a matter of some debate. A number of researchers report that young infants show evidence of global processing by distinguishing global forms such as Gabor contours in noise, Navon letters, and illusory shapes (Bertenthal et al, 1980; Ghim & Eimas, 1988; Kavsek, 2002; Csibra, 2001; Gerhardstein et al, 2004; Otsuka et al, 2004; Bulf et al, 2009; Bremner et al, 2012). Indeed, Freeseman, Colombo, & Coldren (1993), studying 4-month-olds, concluded that global processing is evident before local processing.…”
Section: Local To Global Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this profile for the later development of global perceptual abilities is a matter of some debate. A number of researchers report that young infants show evidence of global processing by distinguishing global forms such as Gabor contours in noise, Navon letters, and illusory shapes (Bertenthal et al, 1980; Ghim & Eimas, 1988; Kavsek, 2002; Csibra, 2001; Gerhardstein et al, 2004; Otsuka et al, 2004; Bulf et al, 2009; Bremner et al, 2012). Indeed, Freeseman, Colombo, & Coldren (1993), studying 4-month-olds, concluded that global processing is evident before local processing.…”
Section: Local To Global Processingmentioning
confidence: 99%
“…Based on habituation and looking time methods, infants appear to perceive KIC figures, although researchers disagree as to the age at which this global perceptual ability is evident (range: 1 month to 8 months; Treiber & Wilcox, 1980; Bertenthal et al, 1980; Csibra, 2001; Otsuka et al, 2004; Bulf et al, 2009; Bremner et al, 2012). Some researchers have questioned whether the looking-time data actually indicate perception of the illusory shape or simply a novelty preference, a stimulus-related preference, or some other variable (Colombo et al, 1988; Freeseman et al, 1993; Kavsek & Yonas, 2006; Bulf et al, 2009; Sato et al, 2013), but other researchers argue that appropriate control conditions explicitly address potential confounding variables in static (Otsuka et al, 2008) and dynamic illusory displays (Curran et al, 1999; Kavsek & Yonas, 2006; Sato et al, 2013).…”
Section: Local To Global Processingmentioning
confidence: 99%
“…For example, Watanabe and Oyama (1988) found that Kanizsa illusory squares were perceived as stronger (e.g., greater contrast and clarity) when proximity between the four elements was high (see also Shipley and Kellman, 1992; Hadad et al, 2010b). Indeed, 4-month old infants perceive an illusory contour formed by a Kanizsa square as an occluding object only when proximity was high and the square formed a narrow occluder (Bremner et al, 2012). Thus, the greater dependence upon the proximity heuristic for illusory contours is may reflect limitations in the distance projected by the horizontal connections in the visual system.…”
Section: Path To Object Perceptionmentioning
confidence: 99%
“…The failure of grouping in the control condition suggests that infants could not bridge the contour gaps to construct illusory regions. In prior studies, infants as young as 3 months of age exhibited evidence of perceiving illusory contours (e.g., Bremner, Slater, Johnson, Mason, & Spring, 2012;Ghim, 1990;Hayden et al, 2008). However, other studies indicate that illusory contour formation is not evident until later in life (e.g., Csibra, 2001), and its development continues well into childhood (Palomares, Landau, & Egeth, 2008).…”
Section: Discussionmentioning
confidence: 97%
“…The contradictory evidence in infant studies indicates that illusory contours are perceived by young infants only if there is sufficient information to support contour formation. For instance, in Bremner et al (2012), while 4-month-olds perceived illusory occluding surfaces when both occluding edges and the occlusion of background texture elements were present at the same time, they failed to do so if only one of these cues was present. It appears that the level of information in the control conditions of the present study was similarly not enough for infants to perceive illusory part regions.…”
Section: Discussionmentioning
confidence: 99%